The Existence of Islamic Boarding Schools in Shaping the Character of Students: Between Tradition and Modernization (Case Studies of Mushtofawiyah Islamic Boarding School and Darul Mursyid Islamic Boarding School) - Siregar, Irma Suryani; Arwin, Arwin; Siregar, Erpiana; Siregar, Lina Mayasari (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
Pesantren are the oldest Islamic educational institutions in Indonesia and play a central role in shaping the character of the Muslim generation. Amidst the development of globalization and modern technology, pesantren are required to maintain their Islamic scholarly identity while adapting to the competency requirements of the 21st century. This study analyzes the approach to character building of santri (students) at two types of pesantren in South Tapanuli: Pesantren Mushtofawiyah, which represents traditional pesantren, and Pesantren Darul Mursyid, which represents modern pesantren. Using a qualitative method with a case study design, data was obtained through in-depth interviews, participatory observation, and analysis of curriculum documents and character building programs. The results show that the Mushtofawiyah Islamic Boarding School develops the character of its students through mastery of classical Islamic texts, intense worship, simplicity, discipline, and the exemplary behavior of the kiai, thereby producing students who are religious, humble, and deeply rooted in classical Islamic tradition. In contrast, the Darul Mursyid Islamic boarding school applies an integrative approach that combines religious education, science, technology, foreign languages, and life skills so that students are more adaptive, communicative, and critical. The study concludes that both pesantren play a strategic role, but excel in different aspects. Moderate integration between tradition and modernization is seen as the ideal model for producing a generation of Muslims who are moral, critical, digitally literate, and ready to face global challenges.